TÜRKIYE AND SPAIN RELATIONS (1900-2020) - Mehmet Gündüz (Al-Qanṭara, 2024)
Located at two different ends of the Mediterranean, Spain and Turkey are the gateways to Europe. The first meeting area of the two countries in history has been the Mediterranean. In the 15th and 16th centuries, the two countries faced each other frequently due to the developments in the Mediterranean Basin. The first permanent peace treaty was signed between the two countries in the last quarter of the 18th century. Especially in the 19th century, both countries lost their land and reputation and sought ways to prevent this. In the early 20th century, the two countries, which lost their qualifications as big states, wanted to take their place in the new world with the new regimes they established. After the Second World War, Spain was excluded by the UN. This situation has also affected Turkey-Spain relations. In the 1950s, relations between the two countries increased with various treaties signed at least at the level of Governments. In addition to, Turkey’s support for Spain’s NATO membership Spain’s support for Turkey’s EU membership has developed relations between the two countries. The relations between the two countries, especially after the 1980s tended to increase in general and in the 2000s rose to the highest level.